Designing the Blockchain-Integrated Collaborative E-Payment Framework: A Philosophical Reflection - Naharudin Saadan; Khairil Faizal Khairi; Azuan Ahmad; Agoos Munalis Tahir (Universiti Sains Islam Malaysia, 2025)
The Journal of Muamalat and Islamic Finance Research, Volume 22 Issue2 Page (40–56)